Micro-computed tomography characterisation of the root and canal morphology of mandibular first premolars with deep radicular grooves - Karobari, Mohmed Isaqali (2024)
Sufficient knowledge of root canals and their complexity and variations is essential in achieving a successful root canal treatment. This study aimed to characterise the root and canal morphology of mandibular first premolars with radicular grooves using micro-CT in the Malaysian population using a recently introduced classification system, and visualisation of root canal morphology using direct, microscope and radiography and determine the application of recently introduced classification system in education though a survey. The study included three distinct components: 1) Micro-CT analysis of 133 mandibular first premolars with deep radicular grooves in the Malaysian subpopulation, assessing deep radicular groove characteristics, root canal configurations, accessory canals, isthmus prevalence, and dentinal thickness; 2) Evaluation of the same samples using direct vision, microscopy, and radiography to compare clinical assessment methods with micro-CT findings; 3) A survey study undertaken involving 1082 dental students in Indian dental colleges to gauge their perceptions of applying a recently introduced classification system. Results showed that radicular grooves were predominantly located in the distal aspect (59.1%) and mesial aspect (39.8%). The average measurements for radicular grooves were: CEJ-to-coronal groove distance mean ± SD (4.92± 1.18 mm), apical groove to root apex distance (2.35 ± 1.56 mm), and groove length (6.69 ± 1.42 mm). Average depth of the radicular groove was 1.48 ± 0.54 mm, with variations at different reference levels. Dentinal thickness at the radicular groove was measured at 0.69±0.26 mm internally and 1.15±0.30 mm externally, with variations at different reference levels. Multiple root canal configurations were observed, with the 1MFP1-2 configuration found to be the most common, comprising a frequency of 19.54% of the observed cases. Accessory canal morphology variations were diverse, with no accessory canal (18.0%) and a delta (1MFP(D)) (21.8%) being prevalent. Accessory canals were most located in the apical third (52.29%) and both middle and apical thirds (28.44%). According to Fan et al. (2010) classification, types 2, 3, and 4 isthmuses were observed in varying frequencies. Clinical assessment methods showed significant differences in observed root canal configurations compared to micro-CT imaging (P<0.001). Distribution and percentage of radiograph with micro-CT comparison for examiners 1 and 2 revealed significant differences between the root canal configurations (P<0.001). Dental students' perceptions of the recently introduced classification system in Indian dental colleges were surveyed to assess its practicality and acceptance. Overall, 92.88% and 91.78% of study participants revealed that the Ahmed et al. (2017) classification system to classify the root and canal morphology was much more practical and accurate than that of the Vertucci’s classification system and its additional configurations. In conclusion, the current study showed significant variations in the location of the radicular grooves predominantly situated in the distal aspect with the most common root canal configuration being 1MFP1-2. The most common type of isthmus observed was Type 2. The multiple visualization techniques, including direct vision, microscopy, and radiography comparisons contributed to a more comprehensive understanding of the advantages and limitations of each method, which guide clinicians in choosing the most suitable imaging method for specific cases. In comparison to Vertucci’s classification system and supplementary types, the undergraduate and postgraduate dental students, and interns in India agreed that Ahmed et al. (2017) classification system is more practical and accurate for classifying the root and canal morphology.